Crustal Deformation and Seismicity Modulated by Groundwater Recharge of Karst Aquifers. Issue 22 (26th November 2018) - D'Agostino, N.; Silverii, F.; Amoroso, O.; Convertito, V.; Fiorillo, F.; Ventafridda, G.; Zollo, A.
Abstract: Triggered seismicity in karst regions has been explained assuming the existence of a hydraulically connected fracture system and downward diffusion of surface pore pressures. Karst systems are, in fact, able to swiftly channel large amount of rainfall through networks of conduits increasing the hydraulic head loading upon the fluid‐saturated, poroelastic crust. Here we use Global Positioning System and hydrological and seismicity data to show that poroelastic strain in the shallow crust (0–3.5 km) controls seasonal and multiannual modulation of seismicity along the Irpinia Fault Zone (Southern Italy) without requiring a hydraulically connected fracture system from the surface to hypocentral depths. We suggest that groundwater recharge of karst aquifers along the Irpinia Fault Zone produces stress perturbations large enough to modulate strain accumulation and seismicity and temporarily modify the probability of nucleation of seismic events such as the 1980 Irpinia, M S 6.9, earthquake. Plain Language Summary: Redistribution of water masses on the surface of the Earth has long been known to alter the state of stress in the crust and trigger seismicity. Karst aquifers form in chemically soluble bedrock, mostly carbonate rocks. In these aquifers most of the rain and snowmelt water infiltrates underground and contributes to climatically modulated groundwater recharge. In this study we use Global Positioning System measurements, together with accurate location of earthquakes, to show that crustal deformation and seismicity in the tectonically active Southern Apennines (Italy) are modulated by seasonal and multiannual phases of groundwater recharge of karst aquifers. The small stress variations induced by hydrological forcing add to the long‐term tectonic loading and help to illuminate the behavior of the Irpinia Fault Zone which, on 23 November 1980, produced the largest Italian event in the last 100 years (magnitude 6.9). Key Points: Phases of recharge/discharge of karst aquifers modulate strain and seismicity in the Southern Apennines (Italy) We invert GPS time series to model hydrological stress perturbations by karst aquifers The 1980 Irpinia, M S 6.9, earthquake occurred during favorable hydrological stress conditions